Severe white matter astrocytopathy in CADASIL - Hase, Yoshiki (John Wiley and Sons Inc., 2018)

(untitled) (Brain Pathol)
OBJECTIVES: Cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is characterized by strategic white matter (WM) hyperintensities on MRI. Pathological features include WM degeneration, arteriolosclerosis, lacunar infarcts, and the deposition of granular osmiophilic material. Based on the hypothesis that the gliovascular unit is compromised, we assessed the nature of astrocyte damage in the deep WM of CADASIL subjects. METHODS: We evaluated post‐mortem brains from CADASIL, cerebral small vessel disease, similar age cognitively normal and older control subjects. Standard immunohistochemical, immunofluorescent, and unbiased stereological methods were used to evaluate the distribution of astrocytes, microvessels, and autophagy markers in five different brain regions. RESULTS: Compared to the controls, the deep WM of CADASIL subjects overall showed increased numbers of glial fibrillary acidic protein (GFAP)‐positive clasmatodendritic astrocytes (P=0.037) and a decrease in the percentage of normal appearing astrocytes (P=0.025). In accord with confluent WM hyperintensities, the anterior temporal pole contained abundant clasmatodendritic astrocytes with displaced aquaporin 4 immunoreactivity. Remarkably, we also found strong evidence for the immunolocalization of autophagy markers including microtubule‐associated protein 1, light chain 3 (LC3), and sequestosome 1/p62 and Caspase‐3 in GFAP‐positive clasmatodendritic cells, particularly within perivascular regions of the deep WM. LC3 was co‐localized in more than 90% of the GFAP‐positive clasmatodendrocytes. CONCLUSIONS: Our novel findings show astrocytes undergo autophagy‐like cell death in CADASIL, with the anterior temporal pole being highly vulnerable. We propose astrocytes transform from normal appearing type A to hypertrophic type B and eventually to clasmatodendritic type C cells. These observations also suggest the gliovascular unit of the deep WM is severely impaired in CADASIL.